Forward and Backward Linkages of Economic Sectors and Determination of Leading Sectors in Southeast Aceh Regency - Roza, Denny Febrian; Lubis, Satia Negara; Sihombing, Luhut; Kesuma, Sinar Indra (International Conference on Sciences Development and Technology, 2023)
This study examines the forward and backward linkages of economic sectors in Southeast Aceh Regency, Indonesia, to identify leading sectors that can drive regional economic growth. Using input-output analysis, the research evaluates the interdependence between sectors by assessing how changes in one sector influence others through supply chains (backward linkages) and demand distribution (forward linkages). The findings reveal key sectors with strong linkages, indicating their potential to stimulate economic activity and generate multiplier effects. The study identifies agriculture, mining, and manufacturing as sectors with significant backward linkages, while trade and services exhibit strong forward linkages. Based on these linkages, the research proposes strategic recommendations for prioritizing leading sectors to enhance regional development. The results provide valuable insights for policymakers in Southeast Aceh Regency to design targeted economic policies, optimize resource allocation, and foster sustainable growth. This study contributes to the broader understanding of regional economic dynamics and offers a framework for identifying leading sectors in similar contexts